Penguatan Literasi Data Siswa SMA Wachid Hasyim 2 Taman melalui Pelatihan Excel - Desita Nur Rachmaniar; Rifdatun Ni’mah; Zerlina Agustiya Putri; Sulthan Rafif (Universitas Pahlawan Tuanku Tambusai, 2026)
Data literacy is an essential competency that enables students to understand, process, and interpret information in the digital era. However, the use of computers in schools is often limited to basic activities, resulting in insufficient skills in data processing and visualization. This community service program aimed to strengthen the data literacy of eleventh-grade students at SMA Wachid Hasyim 2 Taman through training in data processing and visualization using Microsoft Excel. The program employed a hands-on practice approach based on the learning-by-doing method, consisting of lectures, guided exercises, case studies, and quizzes for evaluation. A total of 38 students participated in the training, which covered data cleaning, basic data processing techniques, and chart creation and interpretation. The evaluation results showed an average achievement score of 67%, with the highest performance in basic data concepts and data quality (68%). These findings indicate that practice-based training is effective in enhancing students’ data literacy and supporting the development of essential twenty-first-century skills.